2021
DOI: 10.1111/jan.14751
|View full text |Cite
|
Sign up to set email alerts
|

Daily self‐care practices influence exit‐site condition in patients having peritoneal dialysis: A multicenter cross‐sectional survey

Abstract: Aims To investigate practice patterns in exit‐site care and identify the risk factors for exit‐site infection. Design A quantitative cross‐sectional design. Methods Data were collected in 12 peritoneal dialysis (PD) centres in 2018. Daily exit‐site care practice patterns and exit‐site status of patients receiving PD were assessed through interviews and questionnaires. Results/findings Most of the 1,204 patients adhered with the protocols about main aspects of exit‐site care, such as cleansing agents selection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
0
15
0
3
Order By: Relevance
“…Although our center ensured that patients underwent a three-week PD training conducted by nursing staff with the appropriate qualifications and experience during their hospitalization, daily PD catheter exit-site care tends to become more personalized as the PD duration increases. Ding et al reported that the level of adherence to different aspects of exit-site care varies among PD patients 21 . The study found that patient adherence to proper hand hygiene, mask wearing, exit-site observation, secretion examination, and effective communication with PD staff influenced CRI history and exit-site issues.…”
Section: Discussionmentioning
confidence: 99%
“…Although our center ensured that patients underwent a three-week PD training conducted by nursing staff with the appropriate qualifications and experience during their hospitalization, daily PD catheter exit-site care tends to become more personalized as the PD duration increases. Ding et al reported that the level of adherence to different aspects of exit-site care varies among PD patients 21 . The study found that patient adherence to proper hand hygiene, mask wearing, exit-site observation, secretion examination, and effective communication with PD staff influenced CRI history and exit-site issues.…”
Section: Discussionmentioning
confidence: 99%
“…reported that the level of adherence to different aspects of exit-site care varies between PD patients 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The practice of fixing the catheter by waist belt, protective bag or securing the transfer/extension set to the abdomen by adhesive tape is supported by several observational studies on risk factors of exit site infection. A history of catheter pulling injury or traction bleeding, based on multivariate regression analysis, was associated with increased exit site infections in two studies (hazard ratio 1.78, 95% CI 1.02–3.11 19 and 2.44, 95% CI 1.47–4.04 78 ). We believe this recommendation of fixing the PD catheter also aligns with the ISPD and the Global Renal Exercise Network practice recommendations 79 to avoid repetitive rubbing of the catheter site during sports activity, and the use of a belt during sports to provide protection.…”
Section: Prevention Of Catheter-related Infectionsmentioning
confidence: 99%
“…Contrary to the previous recommendation to protect the exit site with dressing material such as sterile gauze coverage, continuing this practice beyond the immediate post-operative period is not supported by one RCT 18 and two observational studies. 78,81 A single-centre, open-label RCT involving 97 participants in Malaysia showed that simple washing and cleansing of the exit site followed by topical mupirocin with or without a dressing cover resulted in similar incidences of catheter-related infection. 18 The exceptionally low exit site infection rate in this study, at 0.05–0.11 episodes per year, could have limited the external validity of their findings.…”
Section: Prevention Of Catheter-related Infectionsmentioning
confidence: 99%